2012
DOI: 10.1007/s11064-012-0909-8
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Rapamycin on MPTP-Induced Parkinsonism in Mice

Abstract: In neurodegenerative disorders such as Parkinson's disease (PD), autophagy is implicated in the process of dopaminergic neuron cell death. The α-synuclein protein is a major component of Lewy bodies and Lewy neurites, and mutations in α-synuclein have been implicated in the etiology of familial PD. The current work investigates the mechanisms underlying the therapeutic effects of the autophagy-stimulating antibiotic rapamycin in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD. Male C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 30 publications
1
61
0
Order By: Relevance
“…NBP can protect against MPP + -induced neurotoxicity via activation of an autophagic process [1,15]. This report strongly suggests that NBP promotes intracellular autophagic activity and subsequently enhances the degradation of α-synuclein.…”
Section: The Effect Of Nbp In Pdmentioning
confidence: 95%
See 2 more Smart Citations
“…NBP can protect against MPP + -induced neurotoxicity via activation of an autophagic process [1,15]. This report strongly suggests that NBP promotes intracellular autophagic activity and subsequently enhances the degradation of α-synuclein.…”
Section: The Effect Of Nbp In Pdmentioning
confidence: 95%
“…Motor symptoms of PD are mainly due to the selective degeneration of substantia nigra dopaminergic neurons in the ventral midbrain, which results in a decrease in dopamine levels in the striatum [14]. α-Synuclein oligomers and aggregates play an important role in the pathogenesis and development process of PD [1,15]. Protein accumulations in cytoplasmic inclusions are called Lewy bodies.…”
Section: The Effect Of Nbp In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Decressac et al [78] showed that the US FDA-approved derivate of rapamycin, temsirolimus alleviated dopaminergic degeneration following AAV a-synuclein injection by inhibiting mTOR receptors and triggering a proautophagy response in Sprague-Dawley rats. Liu et al [79] reported that rapamycin increased dopaminergic neurons survival, decreased a-synuclein immunoreactivity, increased LC3 expression and ameliorated loss of 3,4-dihydroxyphenylacetic acid in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-treated mice. Beside activation of autophagy by inhibiting mTOR receptors, the effect of rapamycin was shown to be associated with the nuclear translocation of the transcriptional factor, TFEB.…”
Section: Role Of Induced Autophagy In Pdmentioning
confidence: 99%
“…Treatment with rapamycin is able to prevent the loss of TH (tyrosine hydroxylase)-positive neurons in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD likely via activation of the autophagic pathway. 6 It is likely that genes specifically expressed in DA neurons to regulate autophagy could be involved in protecting DA neuron loss.…”
Section: Introductionmentioning
confidence: 99%